Conversion efficiency of Si-InGaAs and GaAsP-Si-Ge lateral beam splitting photovoltaic devices. (April 2018) - Bruzzi, Mara; Baldi, Andrea; Carnevale, Ennio A.; Catelani, Maracantonio; Ciani, Lorenzo
Abstract: This paper deals with the development and characterization of two photovoltaic systems based on the lateral beam splitting principle, with components able to convert different spectral bands of the solar radiation. One is based on a Si cell and a InGaAs photodiode coupled through a long-pass dichroic filter with 950 nm cut-off. A second system is working with a Si photodiode coupled with Ge and a GaAsP photodiodes and two long-pass dichroic filters of 600 nm and 950 nm cut-off in cascade. The systems have been tested under illumination with a Sun simulator and under direct solar radiation in various two-terminal configurations. The performance of the two systems have been compared in same illumination conditions. Both systems, as compared with the Si component alone, proved to significantly increase the photovoltaic performance, achieving at best a conversion efficiency of 20%, so almost doubling its efficiency in best cases.